Clinico-epidemiological characteristics of cerebral venous sinus thrombosis in Kenya: a retrospective case series - Siika, Taby; Sokhi, Jaskirat; Hooker, Juzar; Waa, Sheila; Mwirigi, Anne; Shah, Jasmit; Sokhi, Dilraj Singh (Frontiers in Stroke, 2025)
BackgroundCerebral venous sinus thrombosis (CVST) is a rare cause of stroke that is more common in young, especially female, adults and can be challenging to diagnose due to its frequently non-specific presentation and diverse risk factors. Most cases are idiopathic, and international guidelines do not recommend routine investigations for underlying thrombophilia. Timely diagnosis, with prompt neuroimaging and guideline-based treatment, leads to good outcomes. However, in the literature on CVST from sub-Saharan Africa, the gap is substantial, with the few cases described as being related to systemic and/or brain infections. We describe here the largest cohort of CVST from the region with novel findings that may be relevant to everyday clinical practice.MethodsWe conducted a retrospective cross-sectional study of patients diagnosed with CVST from 2010 to 2022 at our tertiary regional neurology referral center in Nairobi, Kenya.ResultsWe identified 122 cases: 67.2% (82/122) were female, 80.3% (98/122) were Black African, and the median (interquartile range) age was 36.8 (31.5–45.7) years. Apart from headaches (86.9%, 106/122), the most common presenting symptoms were visual disturbance (26.2%, 32/122) and seizures (23.8%, 29/122); 11 patients developed seizures later. Intracranial hemorrhage with and without venous infarction occurred in 27.9% (34/122) of patients. New diagnoses of thrombophilia were made in 30.3% (37/122). Other causes were HIV, hepatitis B/C, or other brain infections (18.0%, 22/118); pregnancy, including postpartum (14.6%, 12/82); contraceptive use (8.5%, 7/82); and malignancy (8.1%, 10/122). The most common treatment was with warfarin in 50% (61/122), followed by rivaroxaban (29.5%, 36/122) and dabigatran [14.8% (18/122)]. Complete thrombus resolution occurred in only 53.9% (55/102) at follow-up scanning (at a median of 178 days). In terms of outcomes (modified Rankin Score [mRS]), 32.8% (40/122) had an mRS score = 0, 59.9% (73/122) had an mRS score = 1–2, and there was one fatality who also had concurrent systemic malignancy.ConclusionThrombophilia was more prevalent in our cohort of CVST than infections, which is a novel finding compared to what has been published about CVST from sub-Saharan Africa. Most patients were managed with appropriate anticoagulants, but only about half the patients had complete resolution of the CVST at last follow-up. We therefore recommend that thrombophilia should be routinely investigated in all patients with CVST in our setting.